THE EFFECT OF FINANCIAL RATIO ON CHANGES IN PROFIT OF PT. MAYORA INDAH Tbk - Indrasari, Reni; Alam, Syamsu; Nohongi, Mursalim (Accounting Profession Journal (APAJI), 2024)
Objectives from the study This is For testing the impact of ratio finance on change profit change PT profit Mayora Indah Tbk. Ratio tested in finance in the study This includes the current ratio (CR), return on assets (ROA), return on equity (ROE), and net profit margin (NPM). Kurun time observation in testing This is 10 years, which is from 2013 to 2022. Research This report uses financial data issued and published by PT Mayora Indah Tbk. The method of data analysis is multiple linear regression. Before using this method, this data is tested, especially formerly with an assumption test classic, namely the normality test, heteroscedasticity, multicollinearity, and autocorrelation. Research results show that NPM is influential to Change PT